Compositions of hyaluronic acid and their use alone and in combination with retinoid for improving skin - BENKOSKI, LASZLO; COURE FABIEN; PELLEGRINO, ALESSANDRO; DELISLE ERIC (2024)
The present invention relates to a method of increasing one or more of collagen, elastin, fibronectin and hyaluronic acid gene expression in the skin of a subject, the method comprising topically administering to the subject one or more hyaluronic acid (HA) compounds and retinoid in a composition. The method improves the vision, feel and/or appearance of the skin, hydrates the skin, plums the skin, improves skin elasticity, improves the appearance of fine lines and wrinkles, reduces the depth, length or width of fine lines and wrinkles, and/or smooths the skin. The present invention also relates to cosmetic compositions comprising hyaluronic acid compounds, including hyaluronic acid, wherein the compositions are anhydrous. 本发明涉及增加受用者皮肤中的胶原蛋白、弹性蛋白、纤连蛋白和透明质酸基因表达中的一种或多种的方法，所述方法包括向受用者局部施用一种或多种在组合物中的透明质酸(HA)化合物和类视黄素。所述方法改善皮肤的视觉、感觉和/或外观，使皮肤水合，丰盈皮肤，改善皮肤弹性，改善细纹和皱纹的出现，减少细纹和皱纹的深度、长度或宽度，和/或平滑皮肤。本发明还涉及包含透明质酸化合物的化妆品组合物包括透明质酸的化妆品组合物，其中所述组合物是无水的。